2006
DOI: 10.1097/01.tp.0000229023.38873.c0
|View full text |Cite
|
Sign up to set email alerts
|

The Transgenic Expression of Human CD39 on Murine Islets Inhibits Clotting of Human Blood

Abstract: Platelet activation is believed to play an important role in the triggering of thrombosis of human blood by pig islets. We used a transgenic mouse model to investigate whether overexpression of CD39 (ecto nucleoside triphosphate diphosphohydrolase 1 [ENTPD1], EC 3.6.1.5), an ectonucleotidase that degrades the platelet agonists ATP, could interfere with this process. Islets isolated from CD39 transgenic mice showed 2.4-fold higher NTPDase activity than wild-type controls. When incubated with human blood, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 21 publications
(15 reference statements)
0
56
0
1
Order By: Relevance
“…The human CD39 transgene (hCD39) is under the control of the mouse H-2Kb promoter, which promotes expression on all nucleated cells. The level of CD39 overexpression is increased on circulating cells (as demonstrated by flow cytometry) [4,14] and in solid organs (as demonstrated by immunohistochemistry) such as the heart [4], lung [4], liver [15], pancreatic islets [16], and kidneys, especially on the vasculature [17]. CD39Tg mice have the same phenotype as WT littermates and have similar body weights and breeding patterns [4].…”
Section: Methods Animalsmentioning
confidence: 95%
“…The human CD39 transgene (hCD39) is under the control of the mouse H-2Kb promoter, which promotes expression on all nucleated cells. The level of CD39 overexpression is increased on circulating cells (as demonstrated by flow cytometry) [4,14] and in solid organs (as demonstrated by immunohistochemistry) such as the heart [4], lung [4], liver [15], pancreatic islets [16], and kidneys, especially on the vasculature [17]. CD39Tg mice have the same phenotype as WT littermates and have similar body weights and breeding patterns [4].…”
Section: Methods Animalsmentioning
confidence: 95%
“…A number of proteins, such as APC (25) and CD39 (26), are also possible candidates for use. APC significantly reduced loss of functional islet mass after intraportal transplantation in diabetic mice, and islets from transgenic mice that express CD39 fail to induce coagulation in roughly one-half of the experiments when exposed to human blood.…”
Section: Discussionmentioning
confidence: 99%
“…The thromboregulatory molecule CD39 is an ectonucleotidase that degrades the platelet agonist ATP. Dwyer et al 15 isolated pancreatic islets from hCD39 transgenic mice, incubated them with human blood and analyzed their impact on IBMIR in comparison to WT islets. The results showed that expression of hCD39 on murine islets significantly delayed clotting in human blood.…”
Section: Genetic Engineering For Molecules That Control Coagulation Amentioning
confidence: 99%